An Analysis of Causal Relationships Among the Factors Affecting the Performance of a Service Organization. (March 2021) - Sharma, Garima; Kumar, Pravin
In the present scenario, services have the largest domination in consumers' lives and constitute a large part of the world economy. The researchers and practitioners have given limited research attention to transformative consumer research which affects consumer well-being. In this study, a causal relationship among the factors influencing the performance of an organization providing the transformative services has been analyzed using total interpretive structural modeling (TISM). The factors influencing the services have been identified through the literature review. After identifying the factors, TISM has been used to interpret the direct as well as significant transitive linkages among the factors. The empirical results suggest that top management plays a big role in consumer well-being along with the welfare of society. Devotion toward the well-being of the broader level of society depends on the top management's commitment toward corporate social responsibility and respect for the rule of laws. These are the major factors influencing the performance of the organization other than employee satisfaction, excellent service quality, use of information technology and e-commerce, and so on.